Elemental Boron for Efficient Carbon Dioxide Reduction under Light Irradiation. (24th March 2017) - Liu, Guigao; Meng, Xianguang; Zhang, Huabin; Zhao, Guixia; Pang, Hong; Wang, Tao; Li, Peng; Kako, Tetsuya; Ye, Jinhua
Abstract: The photoreduction of CO2 is attractive for the production of renewable fuels and the mitigation of global warming. Herein, we report an efficient method for CO2 reduction over elemental boron catalysts in the presence of only water and light irradiation through a photothermocatalytic process. Owing to its high solar‐light absorption and effective photothermal conversion, the illuminated boron catalyst experiences remarkable self‐heating. This process favors CO2 activation and also induces localized boron hydrolysis to in situ produce H2 as an active proton source and electron donor for CO2 reduction as well as boron oxides as promoters of CO2 adsorption. These synergistic effects, in combination with the unique catalytic properties of boron, are proposed to account for the efficiency of the CO2 reduction. This study highlights the promise of photothermocatalytic strategies for CO2 conversion and also opens new avenues towards the development of related solar‐energy utilization schemes.